Analisis Pengaruh Green Marketing dan Brand Ambassador Terhadap Keputusan Pembelian Produk Wardah Pada Konsumen Di Pasuruan Raya Dengan Brand Image sebagai Variabel Intervening - Hari Wahyuni (Universitas 45 Surabaya, 2023)
The business world is growing very rapidly, especially the cosmetic industry. One of the companies experiencing competition in marketing their products is Wardah cosmetic products. The purpose of this study is to find out about the influence of green marketing and brand ambassadors on purchasing decisions for Wardah products for consumers in Pasuruan Raya with brand image as an intervening variable. This research is a quantitative study with a sampling technique using purposive sampling method. The population in this study are women who use Wardah products in Pasuruan Raya. Instrument testing used validity and reliability tests, with data analysis techniques using descriptive analysis, multiple linear regression analysis, t test, f test, determinant coefficient and sobel test. The results of the Sub Structural I t test results (Lifestyle and Brand Ambassador on Brand Image) had a positive and significant effect. 2). The results of the Sub Structural t Test II (Lifestyle, Brand Ambassador and Brand Image on Purchasing Decisions) have a positive and significant effect. Based on the Sobel test, the results of equation I show that brand image can mediate green marketing with purchasing decisions. This means that brand image functions as an intervening variable. While the Sobel test, the results of equation II, brand image can mediate brand ambassadors with purchasing decisions. This means that the brand image variable serves as mediating the intervening variable brand image.